Putative roles of terpenoids in primitive membranes - King, Joshua P.; Wang, Anna (Frontiers in Ecology and Evolution, 2023)
Primitive membranes formed from prebiotically available components must have fulfilled certain essential requirements for the continuation and evolution of life. Candidate amphiphiles that can self-assemble into cell-like structures have been shown to be capable of performing many life-like functions, such as straight-chain fatty acids. However, obstacles that preclude a cohesive description from the origins of primitive membranes to the evolution of modern-day cells remain.Terpenoids are uniquely placed in terms of their derivation and chemical motifs to play an important role in primitive membranes, as they do in extant cells. Here, we discuss the principles behind primitive membrane formation and offer a biophysics perspective regarding the potential role of terpenoids in membrane function. By doing so, we identify opportunities in the realm of protocell research.